Egg production and egg quality characteristics of Yoruba, Sussex, and Goliath chickens and their crossbred progenies under humid tropical climate - Ademola, Abimbola Alice; Fayeye, Timothy Rotimi; Akintunde, Adeyinka Oye; Chimezie, Victoria O. (Ovozoa: Journal of Animal Reproduction, 2023)
Yoruba Ecotype Chicken (YEC) is characterized by hardiness, and better adaptation to prevailing tropical environment. However, its poor egg production has hindered its utilization for commercial production. Crossbreeding is a major tool used in improving desired traits in animals. The objective of the study was to evaluate egg production and quality characteristics in YEC and its crosses with Goliath (GG) and Sussex (SS). The study investigated egg production and egg quality characteristics using 120 sixteen-week-old YEC and its crosses. The findings of the study showed that egg parameters were significantly higher (p<0.05) and maturity occurred earlier (154 days) in YECxSS than in YECxYEC (146 days) and other YEC crosses. The study concluded that cross breeding improved egg production of YEC. Crossbred YEC x SS is therefore recommended for egg production in Nigeria.